The easternmost record of Macratriinae LeConte, 1862 (Coleoptera: Anthicidae), with a new species from Fiji and a genus-rank synonymy in Macratriini LeConte, 1862 - Telnov, Dmitry (Zootaxa, 2021)
The easternmost record of Macratria Newman, 1838 from Fiji is presented, and M. fijiana sp. nov. is described and illustrated. Biogeographical patterns and diversity of Pacific Macratriinae are briefly discussed. Additionally, a new genus rank synonymy in Macratriinae is proposed: Thambospasta Werner, 1974 syn. nov. of Salimuzzamania Abdullah, 1968. New combination is made for Salimuzzamania howdeni (Werner, 1974) comb. nov. (from Thambospasta).